ANALISIS PENGARUH PAJAK REKLAME DAN PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA JAMBI PERIODE 2019-2024 - Bella Savitri Hulu; Haviz Taufik; Aditya Pradana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the development, contribution level, and effectiveness of Advertising Tax and Entertainment Tax on Regional Original Income (PAD) in Jambi City during the 2019–2024 period. The research method used is a quantitative method with a descriptive and explanatory verification approach. The sample was determined using thepurposive samplingwith a focus on the realization of targets and revenues from Advertising Tax, Entertainment Tax, and the total PAD of Jambi City. Data analysis tools used include contribution ratio analysis, effectiveness ratio analysis, and descriptive statistical analysis with the help of SPSS software. The results of the study indicate that the contribution of Advertising Tax and Entertainment Tax to the Regional Original Income (PAD) of Jambi City during the 2019–2024 period is categorized as "Very Low." Advertising Tax contributed an average of 2.68%, while Entertainment Tax contributed an average of 2.99%, so these two sectors have not become the main source of regional PAD formation. Meanwhile, in terms of effectiveness, both types of taxes showed quite good performance although fluctuating. The effectiveness of Advertising Tax ranged from the category of ineffective (the lowest 27% in 2023) to very effective (the highest 114% in 2019 and 104% in 2024). On the other hand, the effectiveness of Entertainment Tax declined sharply due to the impact of the COVID-19 pandemic in 2020 to the ineffective category (31%), but managed to recover as the economy improved and returned to the effective category in the following years (reaching 90% in 2024).